Satellite Tagging of Fin Whales off California and Washington in 2010 to Identify Movement Patterns, Habitat Use, and Possible Stock Boundaries - Schorr, Gregory S; Falcone, Erin A; Calambokidis, John; Andrews, Russel D (2010)
Though fin whales from the California/Oregon/Washington stock are listed as endangered under the ESA and depleted under the MMPA, little is known about their movement patterns, habitat preferences, or stock structure within the region. A large number of fin whales were estimated to have been taken in the eastern north Pacific by whaling activities leading to a substantial decline in population estimates (Ohsumi and Wada 1974). The current population estimate for the California/Oregon/Washington stock is 3,454 whales (Carreta et al. 2007) and the population is thought to be increasing, but the observed trends are not significant (Barlow 1994, 1997). Possible threats to this species from anthropogenic sources include ship strikes (e.g. Douglas et al. 2008), fisheries interactions, and interactions with naval training exercises (i.e. sonar, ship strikes, and live fire exercises). A better understanding of fin whale movements, habitat use, and population structure is necessary to more accurately assess the status of this stock and develop management plans to encourage its recovery.